Foreign bank entry and financial development: New evidence on the cherry picking and foreign bank's informational disadvantage phenomena in the MENA countries - Chadi Azmeh (Cogent Economics & Finance, 2018)
This study investigates the impact of foreign banks entry on financial development in the MENA countries. We use the relative number of foreign banks as proxy for foreign banks entry, and liquid liabilities and claims on private sector as share of GDP as proxies for the financial development. We find a positive long-term and significant effect of foreign banks entry on the size and activity of financial development. We also find that the effect of foreign banks entry depends on the time period and the level of economic development. This result seems to suggest that MENA countries should not be taken as one group when studying the impact of financial sector reform on financial development. The impact of foreign bank entry is positive for the 10 richest MENA countries, while it is negative (but not statistically significant) or negligible for the group of less developed MENA countries. The last result indicates that there is a cherry picking phenomenon in less developed MENA countries. The negative effect of foreign banks cherry picking is diminished over time, since the period 2005-2014 show more positive impact of foreign bank entry on financial development, than the period 1995-2004. This result gives evidence that foreign banks need time to overcome informational disadvantage caused by geographical and cultural distance, to expand their lending into soft information borrowers, and to realize the expected positive effect of its entry on financial development in poorest MENA countries.
Keywords: F65; O16; 330; foreign bank entry; financial development; cherry picking; MENA